Thwaites Glacier ice surface speed change from January 2012 to January 2021 - Bevan, Suzanne; Luckman, Adrian; Benn, Douglas (NERC EDS UK Polar Data Centre, 2021)
A map of changes in ice surface speed in metres/year for Thwaites Glacier, West Antarctica, between January 2012 and January 2021. Speeds based on feature tracking of satellite synthetic aperture radar data. The work was funded by NERC projects NE/P011365/1 and NE/S006605/1. : January 2012 speeds were measures using feature-tracking of TerraSAR-X data between a pair of images acquired on 17/01/2012 and 28/01/2012. Speeds were measured at a horizontal resolution of 40 m. Image data were supplied by DLR. The 2021 speeds were measured using feature-tracking Sentinel-1A and Sentinel-1B images and are a mean of all ten 6- or 12-day pairs acquired in January 2021. Speeds were measured at a horizontal resolution of 100 m and oversampled to 40 m before differencing (2021-2012) with the 2012 speeds. Image data were supplied by ESA. : Feature-tracking was carried out using Gamma Remote Sensing software 20190603. : All feature-tracked displacements were filtered twice: first by a signal to noise ratio based on the cross-correlation of image patches, and then according to deviation from the mean displacement within a neighbourhood. The displacements were converted from the SAR image geometry to ground range geometry, and the results geocoded using the RAMP DEM (Liu et al., 2015). N/A values in the difference geotiff are where either the 2012 or 2021 data are missing.